Mammographically detected spicules associated with malignant breast tumors frequently harbor additional tumor foci - Tuomainen Heli; Sudah Mazen; Joukainen Sarianna; Kärjä Vesa; Masarwah Amro; Jokelainen Otto; Okuma Hidemi (Radiology and Oncology)
On imaging, malignant breast masses are commonly associated with spicules. To the best of our knowledge, the clinical significance of such spiculae has not been previously studied, and no surgical guidelines are available for the management of mammographically detected spiculations.